2001
DOI: 10.1111/j.1151-2916.2001.tb01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Low‐Oxygen Silicon Carbide Fibers (Hi‐Nicalon) in Carbon Dioxide

Abstract: Polycarbosilane-derived low-oxygen SiC fibers, Hi-Nicalon, were heat-treated for 36 ks at temperatures from 1273 to 1773 K in CO 2 gas. The oxidation of the fibers was investigated through the examination of mass change, crystal phase, resistivity, morphology, and tensile strength. The mass gain, growth of ␤-SiC crystallites, reduction of resistivity of the fiber core, and formation of protective SiO 2 film were observed for the fibers after heat treatment in CO 2 gas. SiO 2 film crystallized into cristobalite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In Figure , B for Hi‐Nicalon™‐S, Hi‐Nicalon™, Nicalon™, other SiC fibers including Tyranno™, and SiC whiskers are shown as a function of reciprocal oxidation temperature (1/ T ). Q B can be qualitatively compared from the slopes of B vs 1/ T .…”
Section: Resultsmentioning
confidence: 99%
“…In Figure , B for Hi‐Nicalon™‐S, Hi‐Nicalon™, Nicalon™, other SiC fibers including Tyranno™, and SiC whiskers are shown as a function of reciprocal oxidation temperature (1/ T ). Q B can be qualitatively compared from the slopes of B vs 1/ T .…”
Section: Resultsmentioning
confidence: 99%
“…7 However, the extreme oxygen sensitivity of py-C and BN above 500 • C is a major cause for concern in CMCs that typically exhibit low-stress matrix microcracking. 8 Oxidation of the fibre/matrix interface 9 and exposed fibre surfaces [10][11][12][13] may increase τ to such an extent that crack deflection mechanisms at the fibre/matrix interface are suppressed, 14 leading to the formation of an embrittled region characterised by flat fibre fracture surfaces and negligible pullout lengths. 3,15 A related concern for CMCs containing fibres based on the silicon carbide (SiC) system is the formation of an oxide film at the fibre surface, 15 which acts as a flaw population and decreases fibre strength.…”
Section: Introductionmentioning
confidence: 98%
“…This study focuses on temperatures above where this phenomenon dominates, where an external scale forms with attendant strength changes and which is the case in almost all other experimental works. In some of them, it was shown that a significant portion of the strength loss due to oxidation could be recovered if the oxide scale was removed prior to testing the strength . Recent work has shown that the strength may increase in the initial stage where an amorphous scale forms, but beyond a thickness of about 100 nm, the scale formed on a fiber crystallizes and forms cracks during crystallization accompanied by strength loss .…”
Section: The Modelmentioning
confidence: 99%
“…Among the fibers based on Si and C, the state‐of‐the‐art CMCs under consideration use either Hi‐Nicalon ™ (HN) or Hi‐Nicalon ™ Type S (HNS) fibers, and thus, this work will be limited to these fibers . Significant data on the grain growth, scale thicknesses, and strength of these fibers after exposures to thermal and environmental conditions in inert, air and moisture containing air is available . This work exploits these data to develop a data‐driven semiempirical model that can capture all of the existing data toward a predictive model.…”
Section: Introductionmentioning
confidence: 99%